GOOD GOVERNANCE DI BIDANG PEMERINTAHAN DALAM PERSPEKTIF OTONOMI DAERAH - Sugianto (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2017)
In the era of reform As a tangible manifestation of the Implementation of Local Government by promoting the concept of decentralization, regional autonomy is the main topic that must be discussed and implemented in all the administrative arrangements of local government and society. Under Act No. 23 of 2014 in lieu of Law No. 32 of 2004 on Regional Governance, the present era is free from the complicity of executive and legislative interests. Because in the Implementation of Regional Head Election in this case the Governor, Regent and Mayor have become its own regulation that is Law no 10 year 2016, to choose clean regional leader and statesman as a real manifestation through local elections simultaneously